Provision of Dental Care for Special Care Patients in Ireland: A Qualitative and Quantitative Study - Smith, Gillian; Rooney, Yvonne (Trinity Student Medical Journal, 2008)
Background: Special care dentistry (SCD) is becoming an important part of dentistry in Ireland. The aim of the study is to assess the provision of dental services for special care patients (SCP) by general dental practitioners (GDP) in Ireland and to evaluate the previous training background and determine the type of additional education or training required by GDPs. Methods: A postal and on-line questionnaire was sent to every third member of the Dental Register in Ireland. An analysis of the data was performed using the Statistical Programme for Social Sciences. Results: The response rate to the questionnaire was 35%. The reported level of GDPs with previous training in SCD was 42%, the level expressing a willingness to partake in further training was 62%. Emergency treatments were the most commonly provided service (70%), this was followed by extractions (67%) and restorative treatment (67%). Oral Hygiene Instruction for the carers of SCP was provided by 49% of respondents. An awareness of Disability Act was reported by 26%. Analysis of both the definitions of SCD and the barriers to dental care showed a variety of responses. Additional fees for the treatment of SCP were deemed necessary by 65% of respondents. Conclusions: Whilst the treatment of SCP was reported by the majority of respondents this included primarily emergency services. The need for a greater focus on prevention was highlighted, as was the requirement for improved training of dental practitioners in SCD. Knowledge of the 2005 Disability Act was limited and thus further promotion of its implications for the profession is indicated.